The controller's function : the work of the managerial accountant - Bragg, Steven M. (Hoboken, New Jersey : John Wiley & Sons, 2011)
"This book provides an overview of the functions and responsibilities of the controller/management accountant in a corporation. A controller is the chief accounting executive of a corporation whose chief responsibilities include: (1) planning and control (i.e., budgeting), (2) financial reporting and interpreting, (3) tax administration, (4) management audits and development of accounting systems, and (5) internal/IT audits. Topics covered in this book include: Job description for all positions reporting to the controller. Flex budgeting. Discussion of sales bottlenecks. Role of throughput in determining appropriate overhead levels. Throughput analysis for capital investments. Discussion of the fast close for public companies. Discussion of cost reduction and analysis. Cost Accounting. Accounting for acquisitions."--Provided by publisher